Educating the educator: Evaluation of a standardised format, one-day clinical educator workshop on the assessment of physiotherapy student performance in clinical placement. - Nikki Milne; Ruth Dunwoodie; Garry Kirwin; Tanya Palmer; Julie Gauchwin; Michael Donovan; Carla Dyson; Andrea Hams; Anne Hill (Bond University, 2022)
_Background:_ In Queensland, Australia, physiotherapy students on clinical placements are assessed using the Assessment of Physiotherapy Practice (APP) instrument, by physiotherapists who do not necessarily have a background in education and assessment. Professional development to assist quality assessment processes is currently provided in a variety of formats ranging from online resources to facilitated workshops. However, limited evidence exists regarding best practice methods to support the ongoing training of physiotherapy clinical educators. The aim of this study was to: i) determine if a one-day clinical education workshop can change the perceived knowledge, skills and attributes and overall confidence in ability to undertake a standardised assessment of student performance on clinical placement and; ii) identify if the training format used in the one-day workshop was perceived to be effective in assisting participants with improving their understanding and use of the APP. _Methods:_ Participants attended a single day face-to-face workshop which consisted of standardised content, practical simulated activities and a process of calibrating participants understanding of the assessment standards when applying the APP instrument. Pre and post workshops surveys were administered to participants of the workshop on the day and later analysed using related samples Wilcoxon Signed rank tests to explore pre to post differences in knowledge, skills, attributes, and confidence. _Results:_ Data from 109 clinical educator participants (mean age: 30.25 years) who attended the one-day face-to-face workshop was analysed (79 females; 30 males). After attending the workshop, participants self-reported significantly improved knowledge, skills, attributes, and confidence regarding clinical assessment of physiotherapy students. Additionally, after attending the one-day workshop, clinical educators perceived themselves to be appropriately skilled to undertake a standardised process of assessment when using the APP to indicate a physiotherapy student's clinical performance. _Conclusions:_ The findings from the current study demonstrate that a one-day face-to-face workshop is perceived by clinical educators to be effective for calibrating their understanding and application of the APP instrument to assess physiotherapy students against national entry-level physiotherapy standards.